Impregnação de cério em alumina ativada para a desfluoretação de águas - Sanini, Bruna Machado (2021)
Fluoride ion (F- ) is commonly found in groundwater used for water supply and presents health risks when consumed in excess. Several treatments are studied for water defluoridation, adsorption being one of the most used techniques. Activated alumina is an adsorbent that already has the potential for defluoridation, it can also be submitted to treatments such as impregnation of cations to improve its performance. Cerium (Ce) is rare earth that has an affinity for F- . Thus, in this work, the activated alumina adsorbent impregnated with Ce was prepared and evaluated its potential for batch defluoridation. To prepare the material, different mass ratios and calcination temperatures were tested. An experimental Central Composite Design (CCD) was elaborated to determine the best Fremoval conditions for synthetic water and groundwater samples, in addition to kinetic and isotherm tests. The characterization of activated alumina and activated alumina impregnated with Ce was carried out to analyze changes in the material. The adsorbent that showed the highest adsorption was the one prepared at a mass ratio of 20% cerium (III) nitrate and calcined at 350 °C. The best conditions of the experiment occurred at the central point, at pH 7 and 0.3 g L-1 adsorbent dosage for synthetic sample. The isotherm that best represented the obtained results was Langmuir (R² = 0.781 to 0.958), obtaining Qmax 6.157 mg g-1 . Kinetic balance occurred within the first 10 minutes of contact, is best represented by the pseudo-second-order model (R² = 0.999). The characterization of the material showed changes in pore size, specific surface area, and pore volume, in addition to a good distribution of Ce on the alumina surface. The results show that adsorption with activated alumina modified with Ce is efficient for defluoridation under laboratory conditions and further studies with groundwater are needed to assess the influence of co-existing ions.